Toddler Growth in the Working Area of Kuok Public Health Center, Kampar Regency - Erlinawati, Erlinawati; Apriza, Apriza; Parmin, Joria (Research and Community Service Unit, Poltekkes Kemenkes Kupang, 2022)
Toddler Growth in the Working Area of Kuok Public Health Center, Kampar Regency. The first five years of a child’s life are critical for growth and development because these years assist in generating the adult they will become. Data from WHO discovered that in developing countries, almost 45% of children under five suffer from growth and development disorders. Data from Kuok Public Health Center also demonstrated that in the last three years, there was an increase in the cases of malnutrition were 27 toddlers in 2018. Meanwhile, the were 32 cases in 2019 and 44 in 2020. This study aims to examine factors associated with toddler growth in the working area of Kuok Public Health Center, Kampar Regency. It was a cross-sectional study conducted in the working area of Kuok Public Health Center, Kampar regency, Riau Province. It was performed in January 2021. The samples are 60 toddlers aged 12-60 months with a growth chart. They were selected to be the sample of the study through consecutive sampling. A Chi-square test was administered to evaluate the bivariable. Bivariable analysis displayed a relationship among nutritional status (p-value 0.003, OR 8.321), parenting (p-value 0.003, OR 7.342), exclusive breastfeeding (p-value 0.002, OR 9.201), and parental income (p-value 0.031, OR 4.486) with the growth in toddler. In conclusion, the relationship among nutritional status, parenting, exclusive breastfeeding, and parental income with toddler growth was revealed.